Cytosolic 5′-Nucleotidase II Silencing in a Human Lung Carcinoma Cell Line Opposes Cancer Phenotype with a Concomitant Increase in p53 Phosphorylation - Pesi, Rossana (Int J Mol Sci, 2018)
Purine homeostasis is maintained by a purine cycle in which the regulated member is a cytosolic 5′-nucleotidase II (cN-II) hydrolyzing IMP and GMP. Its expression is particularly high in proliferating cells, indeed high cN-II activity or expression in hematological malignancy has been associated to poor prognosis and chemoresistance. Therefore, a strong interest has grown in developing cN-II inhibitors, as potential drugs alone or in combination with other compounds. As a model to study the effect of cN-II inhibition we utilized a lung carcinoma cell line (A549) in which the enzyme was partially silenced and its low activity conformation was stabilized through incubation with 2-deoxyglucose. We measured nucleotide content, reduced glutathione, activities of enzymes involved in glycolysis and Krebs cycle, protein synthesis, mitochondrial function, cellular proliferation, migration and viability. Our results demonstrate that high cN-II expression is associated with a glycolytic, highly proliferating phenotype, while silencing causes a reduction of proliferation, protein synthesis and migration ability, and an increase of oxidative performances. Similar results were obtained in a human astrocytoma cell line. Moreover, we demonstrate that cN-II silencing is concomitant with p53 phosphorylation, suggesting a possible involvement of this pathway in mediating some of cN-II roles in cancer cell biology.